Penguatan Kemandirian Penyandang Disabilitas melalui Distribusi Alat Bantu di NTB - Rahma Wati; Asyifa Yasmin; Ida Bagus Putu Widana; Nadia Nuril Ferdaus (BADAN PENERBIT STIEPARI PRESS, 2025)
Persons with disabilities are a vulnerable group who often face barriers in mobility, access to public services, and social participation. The Provincial Government of West Nusa Tenggara (NTB), through the Social Affairs Office, initiated an assistive device distribution program as part of the implementation of Law No. 8 of 2016 and Regional Regulation No. 4 of 2019 on the rights of persons with disabilities. This community service activity was carried out during an internship program from February to June 2025 and involved stages of coordination, data observation, field assessment, and direct distribution of assistive devices such as wheelchairs, crutches, and walkers to ten beneficiaries in four target villages. The results showed a significant improvement in the independence and social participation of recipients. Beneficiaries began accessing public facilities independently and became more involved in community activities. However, several challenges remain, including the limited number of assistive devices, incomplete recipient data, and a lack of disability-friendly infrastructure. This program highlights the importance of inclusive approaches, cross-sector collaboration, and strengthened digital data systems to ensure long-term program effectiveness and sustainability. The activity also demonstrates that simple yet targeted interventions can have a profound impact on the quality of life of persons with disabilities and foster a more inclusive and equitable society.